Analysis Impact of the Omnibus Law Job Creation Act on Hajj Pilgrimage Fund Management in Indonesia - Hendy D. MANDEGANI; Siti NURYANAH (Communications of International Proceedings, 2020)
The objective of this research is to analyze the impact of the Omnibus Law Job Creation Taxation Cluster enacted in 2020 on the management of Hajj pilgrimage fund in Indonesia by the Hajj Financial Management Agency (Badan Pengelolaan Keuangan Haji-BPKH). This research was conducted by studying the literature, especially the laws and regulations regarding hajj financial management and taxation. The results show that the tax exemptions in the Omnibus Law of the Taxation Cluster Job Creation Act can provide an increase in the allocation of benefit values to waiting hajj pilgrims. In addition, the tax exemption also potentially increases the economy of Indonesia through increasing the amount of Hajj Fund that can be invested.
Keywords: Omnibus law; Pilgrimage; Tax; Public Finance; Finance.